The lion and the unicorn were fighting for the crown: on-pump versus off-pump coronary-artery bypass grafting - Takagi, Hisato; Mitta, Shohei; Ando, Tomo; Cardiovascular Evidence (ALICE) Group, for the All-Literature Investigation of (Journal of Thoracic Disease; Vol 9, No 12 (December 29, 2017): Journal of Thoracic Disease, 2017)
“…, in the middle of which the Lion and Unicorn were fighting.